Pengaruh Penerapan Sistem Pengendalian Intern, Motivasi Kerja, dan Aksesibilitas Pelaporan Terhadap Kualitas Laporan Keuangan pada Dinas Pekerjaan Umum Kota Padang - Fadhilla Maulani; Rina Asmeri; Meriyani (Fakultas Ekonomi, Universitas Ekasakti, 2024)
The effect of the application of the internal control system, work motivation and reporting accessibility on the quality of the financial statements of the Padang City Public Works Department. This approach uses a quantitative approach, using primary data through a questionnaire. The respondents in this study were the Head of the Finance Division, the Secretary of Finance, Verification (internal Control) and the Staff of the Financial Management Section. The variables used in this study are the Internal Control System, Work Motivation, and Reporting Accessibility as independent variables, and the Quality of Financial Statements as the dependent variable. The method used in analyzing the data is using multiple regression analysis statistics. The results show that the implementation of the internal control system, work motivation and reporting accessibility on the quality of financial reports has no significant effect on the quality of the financial statements of the Padang City Public Works Department.